HUBUNGAN ANTARA KEPUASAN PERNIKAHAN, KOMITMEN BERAGAMA, DAN KOMITMEN PERNIKAHAN DI INDONESIA - Maharti, Hastin Melur; Mansoer, Winarini Wilman (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2018)
This research is aimed to discover the interrelation between marital satisfaction, religiouscommitment and marital commitment globally and based on its types, personal, moral, andstructural. The sampling of the research is 315 persons, with age 20 until 58 years old. The resultof the research shows there is a significant correlation between marital satisfaction and maritalcommitment, religious commitment and marital commitment, marital satisfaction together withreligious commitment and marital commitment. It is also discovers that marital commitmentinfluences personal commitment and moral commitment, while religious commitment influencespersonal commitment, moral commitment, and structural commitment.Keywords: marital satisfaction, religious commitment, marital commitment Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara kepuasan pernikahan, komitmen beragama, dan komitmen pernikahan secara global dan menurut tipenya, komitmen personal, moral, dan struktural. Partisipan penelitian ini adalah berjumlah 315 orang, berusia 20 hingga 58 tahun. Hasil penelitian ini menunjukan bahwa terdapat hubungan signifikan antara kepuasan pernikahan dan komitmen pernikahan, komitmen beragama dan komitmen pernikahan, kepuasan pernikahan bersama dengan komitmen beragama dan komitmen pernikahan. Juga diketahui bahwa kepuasan pernikahan memiliki pengaruh terhadap komitmen personal dan komitmen moral. Sementara komitmen beragama memiliki pengaruh terhadap komitmen personal, komitmen moral, dan komitmen struktural. Kata kunci: kepuasan pernikahan, komitmen beragama, komitmen pernikahan References Abbott, D., Berry, M. and Meredith, W. (1990). Religious Belief and Practice: A Potential Assetin Helping Families. Family Relations, 39(4), p.443.Adams, J. M. & Jones, W. H. (1999). Interpersonal commitment in historichal perspectives. InHandbook of Interpersonal Commitment and Relationship Stability. New York: SpringerScience+Business Media.Agnew, H. (2009). Commitment, Theories and Typologies. Department of PsychologicalSciences Faculty Publications. Diunduh dari: http://docs.lib.purdue.edu/psychpubs/28Allgood, S. M., Harris, S.,Skogrand, L., & Lee, T.R. (2008). Marital commitment andreligiosity in a religiously homogenous population. Marriage & Family Review, 45(1),52-67. doi: 10.1080/01494920802537472.Amato, P. R. 2010. Research on divorce: continuing developments and newtrends. Journal ofMarriage and Family 72(3): 650-666. doi:10.1111/j.1741-3737.2010.00723.xAmato, P. and Sobolewski, J. (2001). The Effects of Divorce and Marital Discordon AdultChildren's Psychological Well-Being. American SociologicalReview, 66(6), p.900.Andrea, S.G. (2014). Hubungan antara religiositas dan komitmen pernikahan pada individuyang menikah melalui ta’aruf. Skripsi. Depok: Fakultas Psikologi Universitas Indonesia.Argue, A., Johnson, D. and White, L. (1999). Age and Religiosity: Evidence froma Three-WavePanel Analysis. Journal for the Scientific Study of Religion, 38(3), p.423.Aron, A., Aron, E. and Smollan, D. (1992). Inclusion of Other in the Self Scaleand the structureof interpersonal closeness. Journal of Personality and Social Psychology, 63(4), pp.596- 612.Arriaga, X. and Agnew, C. (2001). Being Committed: Affective, Cognitive, and ConativeComponents of Relationship Commitment. Personality and Social Psychology Bulletin, 27(9), pp.1190-1203.Benokraitis, N. (1996). Marriages and families. Upper Saddle River, N.J.: Prentice Hall.Beveridge, A., Campbell, A., Converse, P. and Rodgers, W. (1976). The Quality of AmericanLife: Perceptions, Evaluations, and Satisfactions. Political Science Quarterly, 91(3),p.529.Bilqisthi, H. (2014). Hubungan antara komitmen pernikahan dengan kepuasanpernikahan padaindividu yang menikah melalui ta’aruf. Skripsi. Depok: Fakultas Psikologi UniversitasIndonesia.Bimas Islam Dalam Angka. (2012). Kementerian Agama Republik Indonesia.www.bimasislam.kemenag.go.idBKKBN (2011, Desember). Policy brief pusat penelitian dan pengembangan kependudukan.20 Februari 2015. http://www.bkkbn.go.id/ViewBerita.aspx?BeritaID=967Badan Pusat Statistik. (2010). Survey agama berdasarkan provinsi di Indonesia. www.bps.go.idBurpee, L. and Langer, E. (2005). Mindfulness and Marital Satisfaction. Journalof AdultDevelopment, 12(1), pp.43-51.Carp, F. and Carp, A. (1982). Test of a Model of Domain Satisfactions and WellBeing: EquityConsiderations. Research on Aging, 4(4), pp.503-522. Cho, D. W. (2014). The influence of religiosity and adult attachment style on maritalsatisfaction among Korean Christian couples living in South Korea. A Dissertation. Liberty University.Chomeya, R. (2010). Quality of psychology test between likert scale 5 and points. Journal ofSocial Sciences, 6 (3), 399-403.Chung, R. H. (2008). Religiosity as predictor of marital commitment andsatisfaction in KoreanAmerican couples. University of Southern CaliforniaClements, R. and Swensen, C. (2000). Commitment to one’s spouse as a predictorof maritalquality among older couples. Curr Psychol, 19(2), pp.110-119.DeGenova, M. and Rice, F. (2005). Intimate relationships, marriages, andfamilies. New York:McGraw-Hill.DeGenova, M. (2008). Intimate relationships, marriages & families. Boston, MA: McGrawHill.Diener, E. (1984). Subjective well-being. Psychological Bulletin, 95(3), pp.542575.Duvall, E. and Miller, B. (1985). Marriage and family development. New York: Harper & Row.Fowers, B. and Olson, D. (1993). ENRICH Marital Satisfaction Scale: A brief research andclinical tool. Journal of Family Psychology, 7(2), pp.176-185.Gravetter, F.J. & Forzano, L.B. (2009). Research methods for the behavioral sciences (Edisike-3). Belmont, CA: Wadsworth.Goltz, J.W. (1987). Correlates in marital commitment. Disertasi Doktoral.Kanada: UniversitasAlberta.Hansen, D., Kelley, H. and Thibaut, J. (1982). Interpersonal Relations: A Theory ofInterdependence. Journal of Marriage and the Family, 44(1), p.246.Hassan, R. (2007). On Being Religious: Patterns of Religious Commitment in MuslimSocieties. The Muslim World, 97(3), pp.437-478.Hatch, R., James, D. and Schumm, W. (1986). Spiritual Intimacy and MaritalSatisfaction. Family Relations, 35(4), p.539.Harris, S. S. (2005). Marital commitment and religiosity in a sample of adults in Utah. AllGraduate Theses and Dissertations. Paper 2851. http://digitalcommons.usu.edu/etd/2851Haseley, J. and Riggs, S. (2006). Marital satisfaction among newly married couples. Denton:University of North Texas.Hawkins, M. (1981). Care of the dying. BMJ, 282(6280), pp.1969-1969.Heaton, T. and Albrecht, S. (1991). Stable Unhappy Marriages. Journal of Marriage and theFamily, 53(3), p.747.Heaton, T., Albrecht, S. and Martin, T. (1985). The Timing of Divorce. Journal of Marriageand the Family, 47(3), p.631.Hoge, D. and Hoge, J. (1984). Period Effects and Specific Age Effects Influencing Values ofAlumni in the Decade after College. Social Forces, 62(4), p.941Impett, E., Beals, K. and Peplau, L. (2001). Testing the investment model of relationshipcommitment and stability in a longitudinal study of married couples. Curr Psychol, 20(4),pp.312-326.Johnson, M. P. (1973). Commitment: A conceptual structure and empirical application. TheSociological Quarterly, 14(3), 395-406.